Maximum Principle for Nonlinear Cooperative Elliptic Systems on RN (Journal of Partial Differential Equations, 2011)
We investigate in this work necessary and sufficient conditions for having a Maximum Principle for a cooperative elliptic system on the whole R^N. Moreover, we prove the existence of solutions by an approximation method for the considered system.
Keywords: Elliptic systems; p-Laplacian operator; principal eigenvalues; Leray-Schauder fixed point; approximation method